2008
DOI: 10.1063/1.2990066
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions and isothermal equations of state of epsilon hexanitrohexaazaisowurtzitane (CL-20)

Abstract: The phase stability of epsilon hexanitrohexaazaisowurtzitane at high pressure and temperature was investigated using synchrotron angle-dispersive x-ray diffraction experiments. The samples were compressed at room temperature using a Merrill-Bassett diamond anvil cell. For high-temperature compression experiments a hydrothermal diamond anvil cell developed by Bassett was used. Pressures and temperatures of around 5 GPa and 175°C, respectively, were achieved. The epsilon phase was determined to be stable under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 12 publications
6
34
0
Order By: Relevance
“…They also noted that the c-axis showed little compression throughout the entire simulated pressure range. Expansion of one of the unit cell axes under pressure has not been evidenced in similar compression experiments on other energetic materials [11,13,14].…”
Section: Heating At Ambient Pressurementioning
confidence: 94%
“…They also noted that the c-axis showed little compression throughout the entire simulated pressure range. Expansion of one of the unit cell axes under pressure has not been evidenced in similar compression experiments on other energetic materials [11,13,14].…”
Section: Heating At Ambient Pressurementioning
confidence: 94%
“…These results indicated that under the same loading conditions, the shock sensitivity of C-1 increases as the temperature is increased from 20 °C to 95 °C. Figure 4 also demonstrates that the initial shock pressures are almost unchanged as the specimen temperature is increased, because the coefficient of thermal expansion for the ε phase of CL-20 is relatively small [8], and the shock impedance of C-1 is almost unchanged in this temperature range. Thus, a small part of the increased sensitivity may be attributed to the increased porosity at higher temperatures, which results in more hot-spot ignition sites under shock compression.…”
Section: Figurementioning
confidence: 70%
“…The temperature of the C-1 discs rose rapidly up to about 120 °C, then slowed until about 130 °C, followed by a steady temperature rise until 142 °C. Previous studies showed that ε-CL-20 remains stable up to 120 °C, and then transforms into the γ phase at 125 °C [8,9]. Thus, the bend in the temperature profile around 125 °C indicates this phase transition.…”
Section: Preheating Experimentsmentioning
confidence: 99%
See 2 more Smart Citations